The affect of employee motivation in Greater Tampin Oto Sdn Bhd / Mohamad Ikram Suman - Suman, Mohamad Ikram (Faculty of Business and Management, 2018)
In this era globalization with the economic situation is up and down, the motivation of the individual will be effected. It can shows either their motivation level is increase or decrease through the job that they perform. This study is conducted to identify the factors that affect employee motivation in Greater Tampin Oto Sdn Bhd. This research was conducted at Greater Tampin Oto Sdn Bhd, Tampin, Negeri Sembilan, which is one of the authorized dealer of Honda in Negeri Sembilan. This particular research is a quantitative kind of research, thus questionnaires are widely used as the method of gathering the needed data, by taking the individual employees as the unit of analysis. For the sampling technique that used is based on sample size of the employees for 40 respondents. Independent variables in this research are monetary instrument, working environment, job description and communication as moderating variable. Meanwhile, employee motivation is the dependent variable. All the data was analyzed and processed by using Statistical Package for Social Science (SPSS) software. Limitations of this study are also identified after the research is completed. There are also suggestions for future research for better understanding in future.